FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN BERAT BAYI LAHIR RENDAH DI DESA KARANGSONG - Mira Aryanti; Dartiwen Dartiwen (JURNAL KESEHATAN INDRA HUSADA, 2022)
ABSTRAC Background: According to the WHO, the results of the MMR policy are 23.88 per 1000 live births, while the IMR is 12.41 per 1000 live births. The Ministry of Health noted that the number of maternal deaths in Indonesia was 4,627 people in 2020. This number increased by 8.92% from the previous year's 4,197 people. Based on data from West Java Province, the Infant Mortality Rate in 2021 was 2672 cases, compared to 2020 there was a decrease of 88 cases. Indramayu District Health Report in 2021 the number of maternal deaths was 42 cases, the number of infant deaths was 170 cases and the largest cause of infant mortality Methods: This research uses descriptive method with cross sectional approach. The data used is secondary data. The population of this study were all mothers who gave birth in Karangsong village totaling 468 mothers, sampling was carried out by simple random sampling method and the sample in this study was 211 mothers. Data analysis in this study was univariate, bivariate and multivariate. Results: From the results of the study, it was found that the incidence of LBW was 22.3%. The results of the study using the Chi Square test, there is 1 variable that is not related to the incidence of low birth weight (LBW) namely education (p-value 0.826) and there are 2 related variables, namely maternal age during pregnancy (p-value 0.020) and gestational age (p-value 0.020). p-value 0.000). Conclusion: There is a significant relationship between maternal age and gestational age with the incidence of low birth weight, and there is no significant relationship between maternal education and the incidence of low birth weight babies. Keywords: Maternal Age, Gestational Age, Education and LBW